2019
DOI: 10.1186/s41747-019-0126-1
|View full text |Cite
|
Sign up to set email alerts
|

HCC screening: assessment of an abbreviated non-contrast MRI protocol

Abstract: BackgroundHepatocellular carcinoma (HCC) guidelines recommend ultrasound screening in high-risk patients. However, in some patients, ultrasound image quality is suboptimal due to factors such as hepatic steatosis, cirrhosis, and confounding lesions. Our aim was to investigate an abbreviated non-contrast magnetic resonance imaging (aNC-MRI) protocol as a potential alternative screening method.MethodsA retrospective study was performed using consecutive liver MRI studies performed over 3 years, with set exclusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
53
1
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 42 publications
0
53
1
2
Order By: Relevance
“…A prospective surveillance study published in 2020 [ 76 ] found that the sensitivity of non-contrast MRI for diagnosing HCC was 77.1%-79.1%, with a specificity of 97.9%. This result is somewhat different from those of previous studies that analyzed the accuracy of non-contrast MRI (sensitivity, 82.9%-91.7%; specificity, 76.4%-90.7%), but those studies were retrospective in nature or were performed in a diagnostic setting [ 77 - 79 ]. Moreover, a recent comparative study simulating HCC surveillance reported similar sensitivity and specificity between non-contrast MRI and abbreviated MRI using gadoxetic acid [ 80 ].…”
Section: Alternative Surveillance Imaging Modalitiescontrasting
confidence: 92%
“…A prospective surveillance study published in 2020 [ 76 ] found that the sensitivity of non-contrast MRI for diagnosing HCC was 77.1%-79.1%, with a specificity of 97.9%. This result is somewhat different from those of previous studies that analyzed the accuracy of non-contrast MRI (sensitivity, 82.9%-91.7%; specificity, 76.4%-90.7%), but those studies were retrospective in nature or were performed in a diagnostic setting [ 77 - 79 ]. Moreover, a recent comparative study simulating HCC surveillance reported similar sensitivity and specificity between non-contrast MRI and abbreviated MRI using gadoxetic acid [ 80 ].…”
Section: Alternative Surveillance Imaging Modalitiescontrasting
confidence: 92%
“…Several papers have investigated abbreviated MRI protocol in cancer detection, including many looking at HCC detection [34][35][36][37][38][39][40][41]. Lee et al [37] compared an abbreviated screening…”
Section: Plos Onementioning
confidence: 99%
“…Motivated to provide higher sensitivity than US while avoiding the limitations of CT and conventional MRI, investigators have developed abbreviated MRI (AMRI) protocols that rely on a small number of select sequences specifically tailored for HCC detection [12,[23][24][25][26][27][28][29][30][31][32][33][34][35][36] . The rationale is that reduced scanner time decreases costs and complexity, while improving patient comfort, without significantly compromising HCC detection.…”
Section: Introductionmentioning
confidence: 99%